Synthesis and structure of new two-dimensional group 4 metal palladium sulfides, A2MPd3S6 (A = Rb, M = Hf; A = Cs, M = Zr, Hf) - Yoon, Woojin; Park, Hyeongyu; Bae, Sanghyun; Dong, Yongkwan; Yun, Hoseop (Bulletin of the Korean Chemical Society, 2022)
A series of new quaternary group 4 metal palladium sulfides, A2MPd3S6 (A = Rb, M = Hf; A = Cs, M = Zr, Hf) have been prepared from elements with the use of alkali metal halide fluxes and they are structurally characterized by single crystal x-ray diffraction methods. They are isostructural and the structure of the title compounds consists of anionic (Formula presented.) [MPd3S62−] slabs and alkali metal ions. In the slab, the group 4 metals are surrounded by six S atoms in a trigonal prismatic fashion and the Pd atoms are coordinated with four S atoms in square planar fashion. Two hexagons made of six edge-sharing square planar PdS4 are interconnected by two trigonal prismatic MS6 to form the basic repeating unit, M2Pd12S28. These are linked together to form the infinite two-dimensional (Formula presented.) [MPd3S62−] slabs. These slabs stack on top of each other and they are separated by alkali metal cations. There is no strong S-S bonding interaction in this phase and the charge valence of the title compounds could be expressed as [A+]2[M4+][Pd2+]3[S2−]6 (A = Rb, M = Hf; A = Cs, M = Zr, Hf).
Keywords: Alkali metal halides; Alkali-metal ions; Edge sharing; Group 4; Isostructural; Pd atoms; Repeating unit; Single crystal X-ray diffraction method; Title compounds; Two-dimensional; crystal structure; transition metal palladium sulfide; two-dimensional layer